2010
DOI: 10.1080/17543261003736010
|View full text |Cite
|
Sign up to set email alerts
|

Examination of issues affecting the teaching and learning of large cohorts within practical-based subjects

Abstract: The aim of this work is to advance the teaching and learning of practical based subjects in the Higher Education (HE) sector. Part of the study involved the development of a model that enhanced the teaching and learning of textiles within large groups of clothing design learners. This paper begins by reviewing current literature regarding adult learning. The middle section discusses the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…See Table . Questions were developed based on previous studies which identified students’ learning experiences and reactions when new teaching strategies were implemented (Park et al., ; Power, ). This also allowed researchers to evaluate the degree to which collaborative instruction increased student learning throughout the five AD stages.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…See Table . Questions were developed based on previous studies which identified students’ learning experiences and reactions when new teaching strategies were implemented (Park et al., ; Power, ). This also allowed researchers to evaluate the degree to which collaborative instruction increased student learning throughout the five AD stages.…”
Section: Methodsmentioning
confidence: 99%
“…One suggested assessment was to collect feedback from students (Butler et al, 2005;Zuo & MaloneBeach, 2010). Previous studies have also conducted pretest and posttests to evaluate their new materials or approaches (Hodges et al, 2011) and the studies have collected student-generated responses regarding new teaching practices (Gam & Banning, 2011;Power, 2010).…”
Section: Instrumentmentioning
confidence: 99%
“…The main study was conducted over a period of three consecutive years (2009-2010, 2010-2011, 2011-2012) whilst employed at Manchester Metropolitan University. The curriculum development is well documented in previous publications (Power, 2010a;Power 2012a) and is based around the principle of producing industry-ready graduates possessing the necessary employability and technical skills. The unit of study was an advanced product development unit and the learning objective was to synthesize, critically analyse and evaluate novel, emerging and new technologies in relation to a specific end product.…”
Section: The Studymentioning
confidence: 99%
“…It will thus be interesting to explore how active learning approaches can be effectively and efficiently implemented in a large-size fashion and textiles supply chain management class. Prior research by Power [6] can provide valuable reference.…”
Section: Fashion Textiles Departments Usually Have Quite a Large Intakementioning
confidence: 99%